Accuracy and reliability of enamel and dentin thickness measurements on micro-computed tomography and digital periapical radiographs#. (September 2019) - Aktuna Belgın, Ceren; Serindere, Gozde; Orhan, Kaan
Highlights: The use of Micro-CT within forensic practice remains an emerging technology. There was significant differences in the measurements by PR and Micro-CT methods. Micro-CT measurement is highly accurate and reliable as in the conventional method. Micro-CT evaluations can be recommended in the future anthropological studies. Abstract: In the application of scientific human skeletal variation in medico-legal matters, virtual anthropology is the current technique performed to examine skeleton and its body parts. Digital imaging techniques are used in many areas of dentistry and forensic dentistry. Among all digital imaging modalities, digital periapical radiography (PR) are the most widely used, however, new contemporary imaging techniques micro-computed tomography (Micro-CT) can be also used. The aim of this study was to assess the accuracy and reliability of enamel and dentin thickness measurement through intra and inter-observer error analysis, and comparison was made between periapical radiographs and Micro-CT methods. In this study 15 maxillary first premolar were used which extracted for various reasons. Enamel and dentin thicknesses and maximum cervical crown widths (MCCW) of 15 premolar teeth were examined in both Micro-CT and periapical radiographs. The results obtained with the exact maximum cervical crown widths were compared Image J software version. A digital caliper was used to measure the actual MCCW of the teeth. Results exhibited no significant differences in the measurements by the intra or inter-observer error analyses. The intraclass correlation coefficients (ICC) were more than 0.95 by both intra and inter-observer error analyses. There was significant differences in the measurements by PR and Micro-CT methods. By parameters, Micro-CT showed the highest R value (0.962) with the least error in different methods and observers. In conclusion, dentin and enamel measurements by Micro-CT was highly accurate and reliable as in the conventional method (PR). Micro-CT evaluations should be recommended for implementation in the future anthropological studies especially in countries with limited source of dental data.